Recirculation of plasmasphere material during idealized magnetic storms - Bagby-Wright, Christian-Andrew; Welling, Daniel T.; Lopez, Ramon E.; Katus, Roxanne; Walsh, Brian M. (Frontiers in Physics, 2023)
The fate of flux tube material once it is drained out of the plasmasphere through a day side plume remains unknown. One of a few things can happen to the vented plasmasphere material. It can be either swept away by the solar wind and lost to the Earth system, be injected into the ionosphere, or recirculate into the magnetosphere system. Recirculating plasmasphere material could plausibly enter the central plasma sheet and contribute to the ring current. This work uses numerical models to answer this question. Historically this has been a difficult question to answer due to the fact that solar wind, ionosphere, and plasmaspheric plasmas are all dominated by hydrogen making it difficult to distinguish the source of plasma from observation alone. Recent advances in computing have enabled us to answer this question. Using the Space Weather Modeling Framework (SWMF) to couple the Block-Adaptive-Tree-Solar-Roe-Up-Wind-Scheme (BATS-R-US), Dynamic Global Core Plasma Model (DGCPM), and the Ridley Ionosphere Model (RIM), we have tracked the motion of the plasmaspheric material once it leaves the plasmasphere in a self-consistent manner.